Surface and hysteresis properties of lipid interphases composed by head group substituted phosphatidylethanolamines - Salcedo, Cecilia Luciana (2013)
This work analyzes the surface properties of PE-containing membranes modified at the head group region by the addition of methyl and ethyl residues at or near the amine group. These residues alter the lipid–lipid and lipid–water interactions by changes in the hydrogen bonding capability and the charge density of the amine group thus affecting the electrostatic interaction. The results obtained by measuring the dipole potential, the zeta potential, the area per lipid and the compressibility properties allow to conclude that the H-bonding capability prevails in the lipid–lipid interaction. The non polar groups attached to the C2-carbon of the ethanolamine chain introduces a steric hindrance against compression and increases the dipole potential. The analysis of areas suggests that lipids with methylated head groups have a much larger compressibility at expense of the elimination of hydration water, which is congruent with the broader extent of the hysteresis loop.